Análisis de la ventaja comparativa de la producción de banano en la provincia de el oro - Gonzalez Chalan, Anthony Manuel (Machala : Universidad Técnica de Machala, 2022)
The objective of this research is to analyze the comparative advantage of bananas from the province of El Oro compared to other provinces of Ecuador. It begins with knowing the countries that export the most bananas, a general comparison will be made between them and Ecuador and we will know the distance between each of them in terms of percentage; the countries that consume the most bananas will be known, demonstrating that the market is still competitive. Once completed, the research focuses on the national banana, we will know the history of the Ecuadorian banana, its evolution through the years and how it becomes a world reference; we will compare the Gross Domestic Product (GDP) of different years to know the evolution of bananas in the Ecuadorian economy. We will finish by studying and identifying if the province of El Oro has an advantage over the other provinces that also produce bananas. To know this, three variables are analyzed: history, logistics and harvested area.
a presente investigación tiene como objetivo analizar la ventaja comparativa que tiene el banano de la provincia de El Oro frente a las demás provincias del Ecuador. Se comienza con conocer los países que mas exportan banano, se hará una comparación general entre ellos y Ecuador y sabremos la distancia que hay entre cada uno de ellos en términos de porcentaje; se conoce los países que más banano consumen demostrando que el mercado sigue siendo competitivo. Una vez finalizada, la investigación se centra en el banano nacional, se conocerá la historia del banano ecuatoriano, su evolución a través de los años y cómo llega a ser un referente mundial; se compara el Producto Interno Bruto (PIB) de diferentes años para conocer la evolución del banano en la economía ecuatoriana. Terminaremos con estudiar e identificar si la provincia de El Oro tiene ventaja frente a las demás provincias que también producen banano, para saberlo se analiza tres variables que son: la historia, la logística y la superficie cosechada.
Keywords: EXPORTACIÓN; VENTAJA COMPARATIVA; IMPORTACIÓN; BANANA; ECUADOR; AGRÍCOLA